A Conceptual Diagram for Secure Virtual Office Services - Abd Rahman, Nor Azlina; Mago Vistro, Daniel; Jia Le, Tee; Jia Fuei, Cheok (International Journal of Psychosocial Rehabilitation, 2019)
A virtual office is a business platform exists in cyberspace. A virtual office setup allows business owners and employees to work from any location by using technology such as laptop computers and cell phones with internet access. A virtual office can provide significant savings and flexibility compared to renting a traditional office space. This system enables the employer to monitor the employees remotely. Meetings can be conducted via teleconferencing and video conferencing, and documents can be transmitted electronically. Any file transferred will be encrypted to ensure the confidentiality of the data. Integrity check will be done by the system during downloading or receiving the files. The USB ports will be protected to ensure no files can be transferred to the external drive. Digital invoice will be generated instead of manual invoice that need to use digital signature to ensure nonrepudiation. This digital invoice will be more efficient to track any transaction history and at the same time will make stock monitoring will be more efficient as any invoice issued the product, stock will automatically deducted from central database. The user can set the system to notify the user when the available stock less than the amount set by the users. This research paper analyzing the user requirements towards the need of virtual office and conceptual diagram proposed as per overall virtual office services that required by the target users which are small and medium enterprise companies.